Inequality of Thought (IOT) on HIV-Aids and LGBT Through Social Media: A Case Study Gen Z in JPC Foundation - Erlina Puspitaloka Mahadewi; Mohamad Reza Hilmy; Puspita Chairun Nisa; Ario Pamungkas; Suryari Purnama; Mehmet Ozays; Sundring Pantja Djati (CV. Inara, 2025)
The study focused on the purpose of finding out the effect and covering the views and acceptance of LGBT. Jakarta Indonesia is beginning to be seen clearly, especially the large amount of LGBT content both on television stations and on social media at home and abroad. This is very worrying because shows that LGBT is a risk factor for sexually transmitted infections (STIs) including HIV/AIDS. Unsafe sex, drugs, and many sexual partners, make LGBT people more susceptible to STIs. This study aims to determine the description of knowledge about STIs and attitudes towards the LGBT phenomenon in society, especially among young Gen Z people who still have the impact of inequality of thinking in social media. This study is a qualitative descriptive study conducted from October to December 2024. Data collection used a google form questionnaire. The sample consisted of 75 respondents who were members of the community fostered by the